Prevalence and risk factors for pulmonary hypertension in patients with hemoglobin E/β‐thalassemia disease. (10th January 2014) - Atichartakarn, Vichai; Chuncharunee, Suporn; Archararit, Napaporn; Udomsubpayakul, Umaporn; Lee, Ratchanee; Tunhasiriwet, Anusith; Aryurachai, Katcharin
Abstract Objectives To find the prevalence and risk factors of pulmonary hypertension (PHT) in adult patients with hemoglobin E/β‐thalassemia disease (E/β‐Thal). Methods One hundred and ten clinically stable E/β‐Thal outpatients, sixty‐one of whom had undergone splenectomy, were prospectively studied using their clinical profiles, selected blood tests, chest roentgenogram, and transthoracic echocardiogram. Based on the pulmonary artery systolic pressure (PASP) values estimated by the echocardiogram of ≥36 mmHg, they were dichotomized into those with (PHT+) and without (PHT−) PHT. Results PHT was found in 41 (37.3%) patients without gender preponderance. It was not due to the left heart and was not severe (PASP = 46.3 ± 10.4 mmHg). PASP was higher in splenectomized patients (48.0 ± 11 vs. 40.3 ± 4.7 mmHg (P = 0.004)). PHT was found in 32 of 61 (52.5%) splenectomized patients, mostly (53%) in the second decade, and rarely (6.3%) during the first 5 yr after splenectomy. PHT+ patients had more hemolysis (P = 0.001–0.04 depending on the parameters), more asplenic cases (P < 0.001), and higher serum soluble vascular cell adhesion molecule‐1 (sVCAM‐1) and high‐sensitivity C‐reactive protein levels (P = 0.004 and 0.008, respectively). Strong risk factors by univariate analysis were serum sVCAM‐1 levels ≥1600 ng/mL, serum cell‐free Hb ≥ 3 mg/dL, asplenia, and amount of NRBCs/100 WBCs >40. Conclusions Prevalence of PHT in E/β‐Thal patients was 37.3% without gender preponderance. Those with severe hemolysis and asplenia invariably had severer PHT. Strong risk factors were asplenia and associated markedly elevated values of sVCAM‐1, cell‐free Hb, and NRBCs in blood.